The concept of internalisation of the external costs of transport in the EU’ and its impact on the efficiency of transport systems and the performance of logistics supply chains - Grzelakowski, Andrzej S. (Koncepcja internalizacji zewnętrznych kosztów transportu w UE i jej wpływ na wydajność systemów transportu oraz sprawność logistycznych łańcuchów dostaw, 2020)
The subject of the study focuses on the implementation of the concept of internalization of external transport costs in the EU based on the SMCP formula. The research objective is to assess the expected effects this may cause with regard to sustainable mobility standards as well as transport and logistics supply chains operations. These effects are defined in the form of improving their efficiency and effectiveness. Qualitative research methods are principally used. The research results indicate that it will enhance the standards of driving sustainable mobility as well as transport and logistics macro-systems towards rationalization in terms of optimizing transport and inventory costs
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 161-174
Keywords: transport external costs; internalization of external costs; social marginal costs pricing; SMPC; sustainable mobility; green logistics supply chain; koszty zewnętrzne transportu; internalizacja kosztów zewnętrznych; społeczne koszty krańcowe; zrównoważona mobilność; łańcuch dostaw zielonej logistyki